Pendampingan Pembuatan Media Budidaya Cacing Sutera pada Kelompok Pembudidaya Ikan di Kota Sorong - Dwi Indah Widya Yanti; Enny Romanwati; Roger R Tabalessy; Melisa Ch. Masengi; Clara N. Payung (Universitas Kristen Satya Wacana Salatiga, 2020)
Silk worms are natural food for fish that have high protein content. Silk worms are generally obtained by fish farmers from natural catches because no one has cultivated them, due to the lack of knowledge or skills of fish cultivators. The habit of relying on worms from natural supplies makes the availability of silk worms increasingly difficult on the market. For this reason, it is necessary to increase the ability of fish farmers in cultivating silk worms. The method used in community service activities is to provide counseling as well as practice making hairworm cultivation media. Community service activities carried out in the form of counseling and practice of making media for silk worm cultivation have a positive impact on fish cultivator groups. This is because the cultivator group gets new knowledge and can practice it in their cultivation activities. Keyword : media, silk worm, cultivation